Agricultural credit handbook / . - Central Bank of Philippines (Manila, Phillippines : Central Bank of Philippines, 1978)
This book examines the agricultural credit policies of the Central Bank of Philippines in 1979
asm 23/01/2019
Loans
Keywords: Agricultural credit; .; Agricultural credit; Dictionaries, Polyglot